Screening for Atrial Fibrillation using Economical and accurate TechnologY (SAFETY)—a pilot study. Issue 1 (13th January 2017) - Lown, Mark; Yue, Arthur; Lewith, George; Little, Paul; Moore, Mike
Abstract : Introduction: Atrial fibrillation (AF) is a cause of stroke and a marker of atherosclerosis and of all patients with stroke, around 17% have AF. The screening and treatment of AF could prevent about 12% of all strokes. Several relatively low-cost devices with good accuracy now exist which can detect AF including WatchBP and AliveCor. However, they can only measure the ECG or pulse over short time periods. Inexpensive devices such as heart rate monitors, which are widely available, can measure heart rate for prolonged periods and may have potential in screening for AF. This study aims to determine the accuracy of AliveCor and WatchBP along with a bespoke algorithm using a heart rate monitor belt (Polar H7) and a wearable RR interval recorder (Firstbeat Bodyguard 2) for detecting AF during a single screening visit in primary care patients. Methods/analysis: A multicentre case–control diagnostic study comparing the four different devices for the detection of AF with a reference standard consisting of a 12-lead ECG in GP surgeries across Hampshire, UK. We aim to recruit 92 participants with AF and 329 without AF aged 65 years and over. We will ask participants to rate comfort and overall impression for each device. We will collect qualitative data from participants capturing their experience of using wearable devices in order to evaluate acceptability. We will collect data from GPs to determine their views on AF screening. Ethics and dissemination: This protocol was approved by the London—City & East Research Ethics Committee in June 2016. The findings of the trial will be disseminated through peer-reviewed journals, national and international conference presentations and the Atrial Fibrillation Association, UK. Trial registration number: ISRCTN17495003, Pre-results.